La cooperación América Latina y el Caribe-Unión Europea. El difícil camino hacia la asociación estratégica birregional - Lozano Arredondo, Gerardo; Veláquez Castillo , Jesús (Revista Mexicana de Política Exterior, 2022)
Within the framework of the Third LAC-EU Summit, the authors analyze bi-regional relations between these two blocs, particularly as regards the issue of cooperation. The article begins with an overview of the main instruments and mechanisms that comprise the judicial and operative structure of cooperation between the two regions, and the most outstanding contributions of the Guadalajara Summit in this regard. This is followed by a review of issues relating to biregional cooperation, and the content and application of horizontal cooperation programs implemented by the European Commission. According to the authors, among the challenges facing bi-regional cooperation are: the drawing up of a single, long-term strategy and the design of projects that actively involve the two regions, all on a par with the effective application of the principle of bi-regionalism. Finally, they stress the advisability of creating a regional mechanism for dialogue that: guides both regions down the path to a functional strategic partnership; keeps the European Union permanently interested in Latin America, and raises Latin America to the top of the European Union’s list of interests and priorities.